Chlorophyll Fluorescence, Photoinhibition and Abiotic Stress: Does it Make Any Difference the Fact to Be a C3 or C4 Species? - Guidi, Lucia; Lo Piccolo, Ermes; Landi, Marco (Frontiers in Plant Science, 2019)
Chlorophyll fluorescence analysis is one of the most powerful and widely used techniques to study the effect of stresses on the photosynthetic processphotosynthesis and the effects of stresses on this process. From the first utilization, the Fv/Fm ratio has been largely used as a sensitive indicator of plant photosynthetic performance, with optimal values ranging from 0.81 to 0.83 in most plant species. Decreases of this value index are indicative of the reduction of photosystem II (PSII) efficiency, namely photoinhibition. In the last twenty years, application of chlorophyll fluorescence has been largely improved, and many other informative parameters have been established to detect PSII photochemical efficiency and the partitioning of light energy to alternative dissipative mechanisms (qE, energy-dependent quenching; qZ, zeaxanthin-dependent quenching and qI, photoinhibitory quenching; qH, sustained photoprotective antenna quenching; qM, quenching dependent to chloroplast movement; qT, light harvesting complexes II-I state-transition) such as the recently developed “photoprotective power” of non-photochemical quenching (pNPQ). The This review reports a brief description of the main chlorophyll fluorescence parameters and a wide analysis of the current bibliography on the use of different parameters which are useful to detect events of PSII photoinhibition. In addition, in view of the inherent differences in morpho-anatomical, physiological and as well as biochemical features between C3 and C4 speciesmetabolism, possible differences in terms of photoinhibition between C3 and C4 plant species under stress conditions are proposed. The attempt is to highlight the limits of their comparison in terms of susceptibility to photoinhibition and to propose direction of future research which, assisted by chlorophyll fluorescence, should improve the knowledge of the different sensitivity of C3 and C4 to abiotic stressors.